A study on the impact of human resource practices towards organizational commitment at Pejabat Tanah (Tanah Merah) and Pejabat Tanah Machang / Wan Nasuha Wan Ismail - Wan Ismail, Wan Nasuha (2015)
This research attempts to identify which of the dimensions of human resource practices is believed to have the greatest impact towards organizational commitment. (This research was study either the variable is related or not) In this research, the researcher was contributed the questionnaire in order to know the either independent variable (Training, Staffing, Reward System, Team Work and Performance Appraisal) will give impact on dependent variable which is Organizational Commitment. The finding shows that all of variables related each other. The hypothesis testing show those only two hypotheses accepted which is training and performance appraisal. These results were revealed through an investigation that is made by distributing a set of questionnaires that were distributed to 113 respondents at Pejabat Tanah dan Jajahan Tanah Merah and Pejabat Tanah dan Jajahan Machang. Finally, the researcher was discussed about the findings and provides several recommendations derived from the findings.